Screening the Single Euploid Embryo Molecular Genetics in Reproductive Medicine - Sills, E Scott (Springer International Publishing : Imprint: Springer, 2015)
Intended for readers with a background in fertility medicine as well as those less familiar with IVF, this comprehensive work presents an update on preimplantation genetic testing to enable single embryo transfer (SET). An international cast of contributors explains the treatment sequence-from ovulation induction to luteal support-aiming to transfer only one euploid embryo. Applications of molecular techniques for gamete and embryo assessment are fully detailed, with a focus on the strengths and limitations of each. In addition, expert commentary is shared across a range of regulatory challenges associated with embryo screening and cryopreservation. As access to advanced reproductive technology increases against a sharper background of healthcare reform, clinicians, economists, bioethicists and legislators alike will find this new volume relevant and highly accessible.